Synthesis of β-arylated alkylamides via Pd-catalyzed one-pot installation of a directing group and C(sp3)–H arylation - Liu, Yunyun; Zhang, Yi; Cao, Xiaoji; Wan, Jie-Ping (Beilstein Journal of Organic Chemistry, 2016)
The synthesis of β-arylated alkylamides via alkyl C–H bond arylation has been realized by means of direct one-pot reactions of acyl chlorides, aryl iodides and 8-aminoquinoline. Depending on the structure of the starting materials, both single and double β-arylated alkylamides could be accessed.
Keywords: alkylamides; C–H arylation; directing group; in situ installation; one-pot